Distinct conformational changes occur within the intrinsically unstructured pro‐domain of pro‐Nerve Growth Factor in the presence of ATP and Mg2+. (26th January 2023) - Paoletti, Francesca; Covaceuszach, Sonia; Cassetta, Alberto; Calabrese, Antonio N.; Novak, Urban; Konarev, Petr; Grdadolnik, Jože; Lamba, Doriano; Golič Grdadolnik, Simona
Abstract: Nerve growth factor (NGF), the prototypical neurotrophic factor, is involved in the maintenance and growth of specific neuronal populations, whereas its precursor, proNGF, is involved in neuronal apoptosis. Binding of NGF or proNGF to TrkA, p75 NTR, and VP10p receptors triggers complex intracellular signaling pathways that can be modulated by endogenous small‐molecule ligands. Here, we show by isothermal titration calorimetry and NMR that ATP binds to the intrinsically disordered pro‐peptide of proNGF with a micromolar dissociation constant. We demonstrate that Mg 2+, known to play a physiological role in neurons, modulates the ATP/proNGF interaction. An integrative structural biophysics analysis by small angle X‐ray scattering and hydrogen‐deuterium exchange mass spectrometry unveils that ATP binding induces a conformational rearrangement of the flexible pro‐peptide domain of proNGF. This suggests that ATP may act as an allosteric modulator of the overall proNGF conformation, whose likely distinct biological activity may ultimately affect its physiological homeostasis.